Overexpression of Reelin Prevents the Manifestation of Behavioral Phenotypes Related to Schizophrenia and Bipolar Disorder - Teixeira, Cátia M (Nature Publishing Group, 2011)
Despite the impact of schizophrenia and mood disorders, which in extreme cases can lead to death, recent decades have brought little progress in the development of new treatments. Recent studies have shown that Reelin, an extracellular protein that is critical for neuronal development, is reduced in schizophrenia and bipolar disorder patients. However, data on a causal or protective role of Reelin in psychiatric diseases is scarce. In order to study the direct influence of Reelin's levels on behavior, we subjected two mouse lines, in which Reelin levels are either reduced (Reelin heterozygous mice) or increased (Reelin overexpressing mice), to a battery of behavioral tests: open-field, black–white box, novelty-suppressed-feeding, forced-swim-test, chronic corticosterone treatment followed by forced-swim-test, cocaine sensitization and pre-pulse inhibition (PPI) deficits induced by N-methyl--aspartate (NMDA) antagonists. These tests were designed to model some aspects of psychiatric disorders such as schizophrenia, mood, and anxiety disorders. We found no differences between Reeler heterozygous mice and their wild-type littermates. However, Reelin overexpression in the mouse forebrain reduced the time spent floating in the forced-swim-test in mice subjected to chronic corticosterone treatment, reduced behavioral sensitization to cocaine, and reduced PPI deficits induced by a NMDA antagonist. In addition, we demonstrate that while stress increased NMDA NR2B-mediated synaptic transmission, known to be implicated in depression, Reelin overexpression significantly reduced it. Together, these results point to the Reelin signaling pathway as a relevant drug target for the treatment of a range of psychiatric disorders.